Experimental pain in the stomach: a model based on electrical stimulation guided by gastroscopy. Issue 6 (1st December 1997) - Drewes, A M; Arendt-Nielsen, L; Jensen, J H; Hansen, J B; Krarup, H B; Tage-Jensen, U
Abstract : Background —Abdominal pain is often variable in intensity and difficult to characterise due to its referred pain pattern. Clinical pain is furthermore confounded by various emotional and cognitive factors. Aims —To develop and apply an experimental model to induce localised gastric pain. Subjects —Twelve healthy male volunteers. Methods —Stimulating electrodes were mounted on a biopsy forceps and electric stimuli were delivered during gastroscopy. Single, five repeated, and continuous stimuli were given at four locations in the stomach. Pain detection thresholds and pain intensities were assessed together with localisation of the referred pain area. Results —Pain detection thresholds were higher in the prepyloric region compared with those obtained at the lesser and greater curvature. Increasing stimulus intensity resulted in augmented pain perception and repeated stimuli elicited pain at a lower stimulus intensity than single stimuli. Continuous stimuli evoked constant (33%), increasing (33%), or decreasing (33%) pain. The localisation of referred pain varied considerably in the subjects. Conclusions —The model seems relevant to study basic pain mechanisms elicited by localised stimuli in the stomach. The experimental data support the premise that a gastric focus should always be suspected in patients referred with different kinds of abdominal pain.